Dark seasons enhance brain and brown adipose tissue interactions related to mu-opioid receptor signaling - Sun, Lihua; Landau, Anne M.; Tang, Jing; Roivainen, Anne (Springer Nature, 2025)
Purpose
Prior studies reveal seasonal variations of mu-opioid receptor (MOR) signaling in both the brain and the brown adipose tissue (BAT). However, the potential seasonality effect on brain-BAT interactions, related to this signaling pathway, remains unknown. Understanding this dynamic seasonal rhythm may provide novel insights into seasonal affective changes and related psychiatric disorders.
Methods
Nine adult rats (6 males and 3 females) were housed under standard conditions with photoperiodic cycles simulating local seasonal changes. The rats underwent repeated [11C]carfentanil PET imaging to assess MOR availability in the brain and BAT. Partial Least Squares Regression (PLSR) analysis was applied to evaluate the predictability of brain MOR availability on corresponding BAT measures. Latent variables in the PLSR models were eventually categorized by photoperiod.
Results
PLSR models indicated that brain MOR availability considerably accounted for the variance of MOR levels in the BAT (22.82%), comparable to age (23%). Models applying different brain regional measures (striatum, neocortex and thalamus) produced consistent latent variables across models. A shorter photoperiod was associated with increased latent variable (beta = -4.32, 95% CI [-5.30, -3.35]).
Conclusion
These findings suggest that shorter photoperiods enhance, while longer photoperiods reduce, the predictability of brain MOR levels on BAT MOR signaling. These data imply that darker seasons may amplify the interaction between brain activity and peripheral physiology associated with MOR signaling. The adaptability of brain-BAT interactions under stress stimuli offers a new avenue for exploring systems biology.